2018
DOI: 10.4317/jced.54618
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of Oral cancer- A hospital based case control study

Abstract: BackgroundOral cancer is a highly prevalent malignancy in Pakistan. Among various risk factors associated with this neoplasm, habits such as smoked and smokeless tobacco usage, betel quid, and betel nut consumption are the major culprits in our society. In the present study, we aimed to ascertain prevalent risk factors for OC in our population and to compare our findings with healthy controls to establish their significance.Material and MethodsA hospital-based case control study was conducted at Dow University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…This study also identified male predilection with a higher mean age at presentation in females which is in concordance with other studies 17,18 . While oral squamous cell carcinoma has reported predilection for tongue in studies from other parts of the world, in the Pakistani population there is a striking predilection for involvement of buccal mucosa in concordance with the present study where buccal mucosa (54%) involvement surpassed tongue (17.3%) involvement significantly [17][18][19][20] . Lymph node involvement is one of the powerful prognostic indicators for metastasis in oral squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…This study also identified male predilection with a higher mean age at presentation in females which is in concordance with other studies 17,18 . While oral squamous cell carcinoma has reported predilection for tongue in studies from other parts of the world, in the Pakistani population there is a striking predilection for involvement of buccal mucosa in concordance with the present study where buccal mucosa (54%) involvement surpassed tongue (17.3%) involvement significantly [17][18][19][20] . Lymph node involvement is one of the powerful prognostic indicators for metastasis in oral squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, the association between the usage of smokeless tobacco products (gutka, paan, naswar) and oral inflammation was significant. 19 Few Pakistani studies, [20][21][22] also support our finding. In one study by Abbas et al in 2014, it was reported that almost 34% of tobacco users were not educated, and more than 80% were diagnosed with HNCs.…”
Section: Discussionsupporting
confidence: 85%
“…Important factors to consider in this regard are lack of awareness, limited diagnostic tools, low socioeconomic conditions and late presentation. The proportion of smokeless tobacco consumption is also high in Pakistan, and the majority of the people consume smokeless tobacco due 11 among cases and 37%, 11 among healthy controls, power of test 80%and 95% confidence level. The estimated sample size came out as 76 cases and 76 in controls, but we have included 150 cases and 150 controls for the adequacy of results.…”
Section: Introductionmentioning
confidence: 99%
“…Spreading awareness regarding risk factors of oral cancer and prevention efforts can definitely help reduce the incidence of oral cancer. 18 Clinical presentation of oral cancer exhibits substantial variation and can be non-specific, which can hinder diagnosis. Most of the patients with oral cancer presents with signs and symptoms of locally advanced disease.…”
Section: Discussionmentioning
confidence: 99%